Changes in permeability of the alveolar-capillary barrier in firefighters. Issue 9 (September 1985) - Minty, B D; Royston, D; Jones, J G; Smith, D J; Searing, C S; Beeley, M
Abstract : The effect on alveolar-capillary barrier permeability of chronic exposure to a smoke produced by the partial combusion of diesel oil, paraffin, and wood was examined. An index of permeability was determined from the rate of transfer from the lung into the blood of the hydrophilic, labelled chelate 99mTc diethylene triamine penta-acetate (MW 492 dalton). The results of this test were expressed as the half time clearance of the tracer from the lung into the blood (T1/2 LB). The study was carried out at the Royal Naval Firefighting School, HMS Excellent. Permeability index was measured on seven non-smoking naval firefighting instructors who had worked at the school for periods of longer than two and a half months. Tests of airway function and carbon monoxide transfer factor were performed on four of these seven instructors. The results of the permeability index showed a T1/2 LB of 26 min +/- 5 (SEM) which differed significantly from that of normal non-smokers. By contrast all other lung function tests had values within the predicted normal range.